Time-Dependent Effects of Metformin and Olanzapine on the Metabolic System - Kurt, Gizem; Durhan, Seyda T.; Ak, Mehmet; Yanik, Tulin (Pharmacopsychiatry, 2025)
Second-generation antipsychotic drugs, such as olanzapine, have been associated with metabolic side effects including significant weight gain. Recent evidence suggests that this adverse effect may be attenuated by metformin.Male Wistar rats were chronically treated with olanzapine, together with or without metformin, for 7 and 14 weeks. Feeding behavior, food intake, and weight gain were recorded, as well as plasma leptin and triglyceride levels were measured. The expression of hypothalamic candidate genes, Pomc and Npy, involved in appetite and energy balance expressions’ was assessed by quantitative real-time polymerase chain reaction.Olanzapine alone caused significant body weight gain, and the co-administration of metformin for 14 weeks lowered body weight and food intake compared with both the 7-week and control groups. Plasma triglyceride levels did not differ among groups. Leptin levels were significantly higher in the olanzapine-only group and were lower in both metformin-olanzapine groups, more promising in the early co-treatment with metformin. Compared to the control group, the hypothalamus of the olanzapine treatment group exhibited downregulated Pomc expression and upregulated Npy expression.Early co-treatment with metformin significantly mitigated olanzapine-induced weight gain and food intake, demonstrating its potential in preventing metabolic side effects when initiated at the beginning of antipsychotic therapy.
Keywords: olanzapine; metformin; neuropeptide Y; proopiomelanocortin; weight gain.